Radiocarbon Dating and the Protection of Cultural Heritage. Issue 5 (October 2019) - Hajdas, Irka; Jull, A J Timothy; Huysecom, Eric; Mayor, Anne; Renold, Marc-André; Synal, Hans-Arno; Hatté, Christine; Hong, Wan; Chivall, David; Beck, Lucile; Liccioli, Lucia; Fedi, Mariaelena; et al.
ABSTRACT: The modern antiquities market uses radiocarbon ( 14 C) dating to screen for forged objects. Although this fact shows the potential and power of the method, the circumstances where it is applied can be questionable and call for our attention. Here we present an outline of a call to radiocarbon laboratories for due diligence and best practice approaches to the analysis of antique objects requested by non-research clients.